Carboxymethyl Cellulose Based Second Grade Nanofluid around a Horizontal Circular Cylinder - Syazwani, Mohd Zokri; Nur Syamilah, Arifin; Zanariah, Mohd Yusof; Nursyazni, Mohd Sukri; Abdul Rahman, Mohd Kasim; Nur Atikah, Salahudin; Mohd Zuki, Salleh (Semarak Ilmu Publishing, 2022)
Modern challenges include improving heat transmission in a range of industries, including electronics, heat exchangers, bio and chemical reactors, etc. Innovative heat transfer fluids like nanofluids have the potential to increase energy transport effectively. This gain is attained as a result of improved effective thermal conductivity and modified fluid flow dynamics. Therefore, the topic of this paper is improving heat transmission using nanofluids. The objective is to deal with the second grade fluid model passing through a horizontal circular cylinder with mixed convection and suspended nanoparticles. The respective nanoparticles and based fluid of Copper (Cu) and carboxymethyl cellulose (CMC-water) are considered. Both non-dimensional and non-similarity transformation variables are utilized to convert the governing equations to a system of partial differential equations (PDEs). Reduction to ordinary differential equations (ODEs) is attained from the resulting PDEs at the lower stagnation area and then tackled via the Runge-Kutta Fehlberg technique (RKF45) in the Maple software. Graphs are used to illustrate the detailed description of the results of dimensionless parameters like the Biot number, mixed convection, and the second grade parameter. Results show that the fluid slows down while the temperature increases as the value of second grade parameter rises.